KEMAMPUAN BERMAIN RECORDER MELALUI PENDEKATAN KELOMPOK SISWA KELAS V SD ADABIAH PADANG - Amelia Amelia; Idawati Syarif; Esy Maestro (FBS Universitas Negeri Padang, 2013)
Abstract The research aimed at describing the improvement of students ability in playing recorder through group approach students of grade V Nusa at SD Adabiah Padang, in form of Classroom Action Research. The method used was group approach. The research was conducted in two cycles which consisted of planning, action, observation and reflection. The first cycle was done in three meetings and second cycle was done in two meetings. After the research was conducted, the students’ ability in playing recorder which was low at the beginning was gradually improved. It was seen that the data obtained where the students’ ability was only 69 before the research and 88,06 after the research.